First-Year Law Students’ and Teacher’s Questioning in Class - Ribeiro, Luísa; Rosário, Pedro; Moreira, Iněs; Cunha, Rosário Serrão (Frontiers in Psychology, 2019)
Classroom questioning can be considered a key factor in the promotion of student engagement. This case study explored classroom questioning practices and perceptions of a group of 47 first-year law students and their respective teacher. Eight lessons of 90 minutes were observed and audio-taped. Students and the teacher answered a questionnaire. The teacher was also interviewed. The number and type of questions asked by the teacher and by the students were examined. Students and teacher perceptions about the importance of classroom questioning were also analysed. Results pointed out that the teacher and most students consider questioning important or very important for student learning. They also show that, throughout the eight lessons, 913 questions were asked by the teacher and 69 by the students. The number of teacher’s and students’ questions was not balanced, as the teacher was responsible for 93% of the questions. The analysis of the type of questions posed by the teacher and by the students showed the predominance of low-order questions. Therefore, classroom questioning in this case study didn’t seem to promote students’ autonomous thinking. The current study highlights the importance of examining the teacher and students’ patterns of questioning together, analysing its similarities and discrepancies. Implications for teaching, learning, and student engagement at university are discussed.